Tahapan Struktur Alur Cerita Al-Lichyah Az-Zarqā’ karya Kamil Kilani (Analisis Teori Sequence) - Zahra Cahya Putri (An-Nahdah Al-'Arabiyah)
This article aims to analyze the stages of the plot structure of Kamil Kilani's Al-Lichyah Az-Zarqā'. The application of theory is done by using sequence theory or eight sequences. This theory is a more detailed and complex extension of Syd Field's three-act theory. The method used is descriptive qualitative with the technique of quoting sentences that are in accordance with the theory of eight sequences in Kamil Kilani's Al-Lichyah Az-Zarqā'. The results obtained from this study are that Kamil Kilani's Al-Lichyah Az-Zarqā' can be applied and analyzed using sequence theory which shows that the chapters in a story are not meant to inhibit creativity, but make the story more systematic.